Uji Aktivitas Antioksidan dari Ekstrak Kubis Ungu (Brassica oleracea) - Dafnesy Rahmadhani Putri; Sri Benti Etika (MASALIQ, 2025)
Unhealthy lifestyles and environmental conditions have become key contributors to the increased production of free radicals in the body, which are linked to the development of various degenerative diseases. To counteract these effects, the body requires antioxidant compounds capable of neutralizing free radicals. Brassica oleracea (purple cabbage) is a vegetable known to contain bioactive compounds, particularly flavonoids, with potential as natural antioxidants. This study aims to determine the antioxidant activity of concentrated purple cabbage extract. The DPPH (2,2-diphenyl-1-picrylhydrazyl) method was employed, with extraction carried out through maceration using methanol as the solvent. Antioxidant activity was tested at various concentrations to determine the IC₅₀ value. The results showed that purple cabbage extract exhibited moderate antioxidant activity, with an IC₅₀ value of 144.170 mg/L. These findings indicate that purple cabbage holds promise as a natural antioxidant source, with potential applications in functional food and pharmaceutical development.